2011
DOI: 10.1177/1941738111422044
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Grade I and II Hamstring Injuries in Intercollegiate Athletes

Abstract: Background:Hamstring muscle strains represent a common and disabling athletic injury with variable recurrence rates and prolonged recovery times.Objectives:To present the outcomes of a novel rehabilitation protocol for the treatment of proximal hamstring strains in an intercollegiate sporting population and to determine any significant differences in the rate of reinjury and time to return to sport based on patient and injury characteristics.Study Design:Retrospective case series.Methods:A retrospective review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 21 publications
0
33
0
2
Order By: Relevance
“…Hip ROM (SLR) at 2 days after injury 1 Passive SLR test (within 3 days after injury) 28 Knee flexion strength at 2 days after injury 1 Palpated length of the painful area Location of most pain during palpation 4 Region, length, width, depth, volume, and cross-sectional area (MRI at 2, 10, 21, and 42 days) 3 Length of the injury (MRI at a mean 13 weeks [range, 1-52 weeks]) 4 Length of the injured area (US at 1-10 days after injury) 20 Distance to the ischial tuberosity (MRI at a mean 13 weeks [range, 1-52 weeks]) 4 Individual vs team sports 4 Location of the hamstring injury (MRI within 3 days) 6 Injured area 15,[26][27][28] Age 6,13 Muscle involved (MRI) 7,10,13,26 Injury to the kicking leg vs supporting leg 10 Side (right, left) 13 Single vs double muscle involvement (MRI within 24-72 hours) 11 Previous hamstring injury 11,13 Sex 13 Sport 13 Degree of injury (I, II [clinically graded]) 13 Frequency of physical therapy sessions 17 Positive vs negative US findings 20 Static stretching, isolated progressive hamstring resistance vs progressive agility and trunk stabilization exercise rehabilitation program 24 Progressive agility and trunk stabilization vs progressive running and eccentric strengthening rehabilitation program 25 Injury involving both the muscle belly and musculotendinous junction (MRI within 3 days) 26 Ganglion-like fluid collection (MRI within 3 days) 26 Hemorrhage-like signal intensity (MRI within 3 days) 26 Time taken to ascend stairs without pain 28 Slump test (within 3 days after injury) 28 Active knee extension test (within 3 days after injury) 28…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Hip ROM (SLR) at 2 days after injury 1 Passive SLR test (within 3 days after injury) 28 Knee flexion strength at 2 days after injury 1 Palpated length of the painful area Location of most pain during palpation 4 Region, length, width, depth, volume, and cross-sectional area (MRI at 2, 10, 21, and 42 days) 3 Length of the injury (MRI at a mean 13 weeks [range, 1-52 weeks]) 4 Length of the injured area (US at 1-10 days after injury) 20 Distance to the ischial tuberosity (MRI at a mean 13 weeks [range, 1-52 weeks]) 4 Individual vs team sports 4 Location of the hamstring injury (MRI within 3 days) 6 Injured area 15,[26][27][28] Age 6,13 Muscle involved (MRI) 7,10,13,26 Injury to the kicking leg vs supporting leg 10 Side (right, left) 13 Single vs double muscle involvement (MRI within 24-72 hours) 11 Previous hamstring injury 11,13 Sex 13 Sport 13 Degree of injury (I, II [clinically graded]) 13 Frequency of physical therapy sessions 17 Positive vs negative US findings 20 Static stretching, isolated progressive hamstring resistance vs progressive agility and trunk stabilization exercise rehabilitation program 24 Progressive agility and trunk stabilization vs progressive running and eccentric strengthening rehabilitation program 25 Injury involving both the muscle belly and musculotendinous junction (MRI within 3 days) 26 Ganglion-like fluid collection (MRI within 3 days) 26 Hemorrhage-like signal intensity (MRI within 3 days) 26 Time taken to ascend stairs without pain 28 Slump test (within 3 days after injury) 28 Active knee extension test (within 3 days after injury) 28…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Time to RTS after acute hamstring injuries varies substantially between studies, from an average of 11.3 days59 to 50 weeks 60. Among professional football players, the mean lay-off time was 18±1961 and 19±1762 days.…”
Section: Section 3: What Evidence Do We Have To Inform the Clinician'mentioning
confidence: 99%
“…Many classification systems have been presented in the literature based on clinical examination findings, 20,21 available ROM, 10,22 type of injury (functional or structural), 23 and imaging findings 24 ; yet a validated grading system does not exist, 21 and no system correlates with prognosis. 25 Furthermore, researchers 26 have shown no difference in time to RTP for patients with a grade 1 versus grade 2 HSI based on a traditional 3-point clinical grading scale. Therefore, our survey did not differentiate among grades of HSIs in our analysis of clinical practice patterns, which is a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] The remaining methods (knee immobilizer and joint mobilizations) had lower use rates, yet some limited support exists for their application. A short period of immobilization after musculoskeletal injury has been recommended 26,40 because it limits connective tissue proliferation, but the ideal period has not been established, as prolonged immobilization is associated with atrophy and decreased strength and flexibility. 40,41 Limited support for joint mobilizations was provided by Cibulka et al 42 who used mobilizations of the sacroiliac joint in patients with HSIs and demonstrated greater peak torque production after injury than in a control group.…”
Section: Use Of Treatment and Rehabilitation Methodsmentioning
confidence: 99%